OP0250 EFFICACY AND SAFETY OF ROMILKIMAB IN DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS (DCSSC): RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED, 24-WEEK, PROOF OF CONCEPT STUDY. (2nd June 2020) - Allanore, Y.; Wung, P.; Soubrane, C.; Esperet, C.; Frederic, M.; Bejuit, R.; Lahmar, A.; Khanna, D.; Denton, C.
Abstract : Background: Systemic sclerosis (SSc) is a progressive, multi-organ disease with limited treatment options. Interleukin-4 (IL-4) and IL-13 have been implicated in the fibrotic pathway and pathogenesis of SSc and are promising targets. Romilkimab (RKB) is an engineered humanized bispecific Ig-G4 antibody that binds and neutralizes both IL-4/IL-13. We report a Phase IIa randomized, double-blind, placebo-controlled trial (NCT02921971, Sanofi funded) employing RKB in SSc. Objectives: To evaluate the efficacy and safety of RKB in dcSSc. Methods: Patients with dcSSc duration ≤36 months, mRSS 10-35, with or without immunosuppressive background therapy were randomized (1:1) to subcutaneous RKB 200mg or placebo (PBO) for 24 weeks and stratified on history of SSc-ILD. Primary endpoint was mean change in mRSS at Week 24 and FVC/DLco and HAQ-DI were secondary endpoints. All analyses used a 1-sided p-value <0.05 as reaching statistical significance. Results: Ninety-seven patients with similar baseline characteristics between arms, including use of background therapy (RKB 59.2% vs. PBO 52.1%) were randomized. Six (12.2%) and 4 (8.3%) patients discontinued study treatment early in the PBO and RKB arms, respectively. Primary endpoint showed an absolute change in mRSS of -2.45 (0.85) and -4.76 (0.86) for PBO and RKB groups, respectively with a difference of -2.31 (1.21) favoring RKB (p=0.029). Subgroup analysis based on background therapy showed a similar treatment effect with a PBO subtracted difference in mRSS of -2.69 (1.83) and -2.38 (1.59), suggesting an additive effect between background therapy and RKB. Secondary endpoints did not show a statistically significant difference between RKB vs. PBO arms, although there was numerically less decline in FVC with RKB with a PBO subtracted difference of 70ml (p=0.06). Exploratory endpoints suggested possible effect of RKB on overall pain, Raynaud's, digital ulcers, and EQ-5D-5L. Post-hoc analysis was undertaken to determine time to progression (first event defined as death, ≥10% relative decline in % predicted FVC, ≥15% relative decline in % predicted DLCO, ≥20% increase or +5 in mRSS, or other events: cardiac, SRC, PAH development) and showed a benefit for RKB (HR: 0.47 p=0.04). Adverse events were balanced between the two groups (RKB 83.3% vs. PBO 83.7%). There were 5 and 4 SAEs in the PBO and RKB arms, respectively. One death occurred in each arm (SRC – RKB, cardiomyopathy – PBO). Conclusion: Patients with dcSSc who were treated with RKB showed a statistically significant reduction in mRSS compared to those receiving PBO. Secondary outcomes were not met, although RKB was associated with a smaller decline in FVC than PBO. Post-hoc analysis showed a possible reduction on time to progression with RKB. RKB was well tolerated with no major safety concerns. References: None. Disclosure of Interests: Yannick Allanore Grant/research support from: Yannick Allanore has received grants from Inventiva, Roche and Sanofi, Consultant of: Yannick Allanore has received fees from Actelion, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Curzion, Inventiva, Roche, Sanofi, Peter Wung Shareholder of: I own Sanofi stock, Employee of: I work for Sanofi, Christina Soubrane Employee of: I work for Sanofi., Corinne Esperet Employee of: I work for Sanofi., MARRACHE Frederic Employee of: I work for Sanofi, Raphael Bejuit Employee of: I work for Sanofi., Amel Lahmar Employee of: I work for Sanofi., Dinesh Khanna Shareholder of: Eicos Sciences, Inc./Civi Biopharma, Inc., Grant/research support from: Dr Khanna was supported by NIH/NIAMS K24AR063120, Consultant of: Acceleron, Actelion, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Corbus Pharmaceuticals, Horizon Therapeutic, Galapagos, Roche/Genentech, GlaxoSmithKline, Mitsubishi Tanabe, Sanofi-Aventis/Genzyme, UCB, Christopher Denton Grant/research support from: GlaxoSmithKline, CSL Behring, and Inventiva, Consultant of: Medscape, Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Corbus Pharmaceuticals, Acceleron, Curzion and Bayer